2012
DOI: 10.1007/s10067-012-2050-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug compliance in patients with systemic scleroderma

Abstract: Although drug compliance is a crucial component of treatment effectiveness in chronic diseases, it has never been evaluated in patients with systemic scleroderma. Therefore, the aim of this descriptive study was to determine the drug compliance rate in systemic scleroderma patients and to identify risk factors for noncompliance in these patients. A cross-sectional observational study was conducted. All patients with systemic scleroderma (n = 41) who visited a rheumatic center and signed an informed consent for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
1
12
0
5
Order By: Relevance
“…To the best of our knowledge, this is the first evaluation of the relationship between drug compliance and QoL among patients with rheumatic diseases. The results of our previous study, performed in SSc patients, indicated no significant relationship between the two factors [13]. However, we decided to verify our results and carry out an extended investigation with various rheu- matic disorders, as there are substantial differences which exist between different rheumatic diseases.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first evaluation of the relationship between drug compliance and QoL among patients with rheumatic diseases. The results of our previous study, performed in SSc patients, indicated no significant relationship between the two factors [13]. However, we decided to verify our results and carry out an extended investigation with various rheu- matic disorders, as there are substantial differences which exist between different rheumatic diseases.…”
Section: Discussionmentioning
confidence: 77%
“…The study was conducted in two phases. In the first phase (January 2010-June 2011), we aimed to collect data on patients with SSc, as data on the compliance of SSc patients were lacking in the literature [13]. In the second phase (October 2011-March 2012), data on patients with RA, JIA and SA were collected.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous studies differed in their conclusions regarding the factors that are associated with nonadherence. Some researchers argued that barriers to adherence should be assessed on an individual basis, 16 , 20 but others identified specific factors associated with adherence in patients with rheumatic diseases, such as education level, marital status, language proficiency, race, comorbidities, high pharmacy costs, taking many pills, number of side effects, missing physician appointments, and quality of life. 21 25 Our results indicate that side effects and use of alternative medicines were associated with nonadherence in patients with rheumatic diseases, in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to (or compliance with) treatment is an essential component of treatment effectiveness in chronic diseases, as non‐adherence may decrease the effectiveness of treatment, increase mortality and morbidity, and increase healthcare costs . However, adherence to treatment is low in chronic diseases as well as inflammatory and autoimmune diseases, so approximately 40–80% of such patients do not adhere to their medications . According to the literature, the rate of non‐adherence in chronic eye diseases like glaucoma is also low and varies between 5–80% and a relationship exists between non‐adherence and progression of visual loss .…”
Section: Introductionmentioning
confidence: 99%